Effects of wastewater filtration on geotextile permeability. Issue 3 (June 2006) - Yaman, C.; Martin, J. P.; Korkut, E.
Abstract : The purpose of this study was to show how the permeability of different types of geotextile behaved when they were subjected to municipal wastewater filtration. The tests were intended to show the clogging potential of geotextiles if they were used for wastewater treatment. The geotextiles filtered organic suspended solids and hosted growth of microorganisms. The test liquid was primary treatment effluent that treated combined sewage (wastewater plus stormwater runoff). The project used 10.16 cm diameter packed columns containing alternating layers of gravel, sand and geotextile filters. The study included four phases. The first phase was intended to measure the baseline permeability of each geotextile used. The second phase was a screening phase to see how the permeability of woven and nonwoven geotextiles changes when they are subjected to wastewater. Phase III was a parametric study to assess the effects of variables on residual permeability. These variables were the number of geotextile filter layers, the hydraulic loading rate (HLR) or flow rate, and provision for passive re-aeration. It was found in the first two phases that only nonwoven geotextiles with complex structures and high internal porosity retained more biomass yet preserved sustainable permeability. A confirmatory final phase was conducted using the best combination of operating variables indicated by the parametric study. It was shown that these variables influence the residual permeability of the geotextile filters tested. The confirmatory final phase included two layers of continuous filament geotextile filters in a granular matrix of decreasing coarseness with depth, maintaining an unsaturated subgrade, and twice daily dose and drain application of primary treatment effluent at a net rate of 365 L/m 2 /day. With this HLR, the composite filter permeability of 0.925 cm/s was sustained with little loss, 0.2%, whereas the control column with no geotextile layer indicated 13% permeability loss. Scanning electron microscope images showed that the biomass morphology was a discontinuous floc entrapped within the geotextile pore structure.